Do difficulties in emotional processing predict procedure pain and shape the patient's colonoscopy experience?. Issue 2 (21st February 2022) - Pontone, Stefano; Lauriola, Marco; Palma, Rossella; Panetta, Cristina; Tomai, Manuela; Baker, Roger
Abstract : Objectives: Pain and fear of colonoscopy are inter-related; they make the colonoscopy experience unpleasant and impede adherence to colorectal cancer screening and prevention campaigns. According to previous research, fear and pain have been found to depend on patients' maladaptive cognitions and exaggerated emotional responses. The present study investigated whether emotional processing difficulties predicted colonoscopy pain and the associated catastrophising thoughts. Design: Prospective, observational, blinded. Method: A sample of 123 patients was assessed for specific emotional processing difficulties (ie, suppression of emotions, unprocessed emotions, failure to control emotions, avoidance of emotional triggers and impoverished emotional experience) and anxiety-related variables (ie, worry, anxiety and depression) before colonoscopy. A trained medical doctor rated patients' behavioural manifestations of pain during colonoscopy. After complete recovery from sedation, the patients rated the endoscopy experience using perceived pain and situation-specific pain catastrophising scales. Results: About half of the patients were above the cut-off for anxiety before the procedure. Notwithstanding sedation, behavioural manifestations of pain during colonoscopy indicated probable or moderate pain for about one-third of the patients. Failure to control emotions, poor emotional experience and avoiding emotional triggers were positively correlated with behavioural manifestations of pain, self-reported pain and pain catastrophising. Regression analyses, controlling for gender, age, colonoscopy experience and sedation, revealed that avoidance of emotional triggers uniquely contributed to predicting pain outcomes. Conclusions: Early identification of emotional processing difficulties associated with pain catastrophising can help define personalised psychological preparation paths to manage negative emotions in patients who fear colonoscopy pain.